Sensitivity analysis of a parabolic trough concentrator with linear V-shape cavity - Rafiei, A. (John Wiley and Sons Ltd, 2020)
In the present investigation, a solar parabolic trough concentrator (PTC) with a linear cavity was examined by using a developed numerical model. More specifically, a V-shape cavity receiver was studied in this work as a new and alternative design. The use of a cavity in a PTC is a very promising idea because it leads to high efficiency and to low investment cost. Up today, the emphasis in the use of cavities is given in dish concentrators and so there is a need for investigation of cavities also in linear concentrators. Different dimensional and operational parameters of the PTC with a V-shape cavity were considered. More specifically, the position, aperture area, and the tube diameter of the V-shape cavity, solar irradiance, inlet temperature level, and mass flow rate were evaluated based on sensitivity analysis. The results revealed that the highest optical performance was attained when the cavity was placed at the PTC focal line. Moreover, it is found that there is an optimum cavity aperture area to determine the greatest thermal efficiency. For the optical errors of 5, 10, 15, 20, and 35Â mrad, the optimum cavity aperture wide was calculated at 5, 5, 6, 7, and 8Â cm, respectively, with the tracking error to be 0Â°. The highest thermal performance has found when the collector operates with low inlet temperature, high flow rate, high solar irradiation level, and small cavity tube diameter. Â© 2020 The Authors. Energy Science & Engineering published by the Society of Chemical Industry and John Wiley & Sons Ltd.